The Strategies of Majelis Tazzkiyah in Enhancing Fiqh Education for Muslim Women in Medan - Syamsiah, Siti; Ritonga, Asnil Aidah (Universitas Pendidikan Indonesia, 2025)
This research aims to examine the strategies and methods, the relevance of fiqh materials, and the role and challenges of the Tazzkiyah Assembly in enhancing fiqh education for Muslim women in Medan, based on the theory of the social role of religious institutions. Using a qualitative approach with field research, data were collected through observations, interviews, and documentation. The study involved 20 informants, including assembly administrators, ustazahs, and regular study participants. Data analysis followed the Miles and Huberman model. The findings reveal that the Tazzkiyah Assembly is highly effective in improving fiqh education through various strategies and methods, including the integration of technology in fiqh learning. The assembly also serves as a platform for the spiritual and social development of Muslim women. However, challenges such as the competence of educators need to be addressed to enhance the quality of learning. This study recommends increasing the number of educators through open recruitment or collaboration with other educational institutions, enabling the Tazzkiyah Assembly to better support fiqh education for Muslim women in Medan.Penelitian ini bertujuan untuk mengkaji strategi dan metode, relevansi materi fikih, serta peran dan tantangan Majelis Tazzkiyah dalam meningkatkan pendidikan fikih bagi Muslimah di Medan berdasarkan teori peran sosial lembaga keagamaan. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi lapangan (field research), dengan data yang diperoleh melalui observasi, wawancara, dan dokumentasi. Informan dalam penelitian ini berjumlah 20 orang, yang terdiri dari pengurus majelis, ustazah, serta peserta rutin kajian, dengan analisis data menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa Majelis Tazzkiyah sangat efektif dalam meningkatkan pendidikan fikih melalui berbagai strategi dan metode, seperti mengintegrasikan teknologi dalam pembelajaran fikih. Majelis ini juga berperan sebagai wadah pengembangan spiritual dan sosial bagi Muslimah. Namun, tantangan seperti kompetensi pendidik perlu diatasi untuk meningkatkan kualitas pembelajaran. Penelitian ini menyarankan pengembangan kuantitas pendidik melalui open recruitment atau kolaborasi dengan lembaga pendidikan lain, agar Majelis Tazzkiyah dapat lebih optimal dalam mendukung pendidikan fikih bagi Muslimah di Medan.